Date palm: an ideal fruit for health and wealth - Singh, R S (Indian Horticulture, 2019)
Among arid fruits, date palm is highly nutritious because of rich source of carbohydrates, minerals, vitamins and anti-oxidants. The tree is hardy to prevailing hot and dry climate, frost, drought and salinity in the arid region. Its fruit is used as fresh and for making value-added products, viz. dry date (chhuhara) , soft date (pind), jam, beverages, wine, etc. Seed is also used for animal, fish and poultry feed, besides oil extraction. Its fruit has religious as well as nutritive significance and is used as energy food across the world. All plant parts are used in various ways for making handicraft items. In semi-arid and arid parts, the area under its cultivation has increased to 20,000 ha. Its productivity is about 9.4 tonnes/ha. It has export potential. The proper marketing and popularization of value-added products will help to fetch more income to farmers in arid region.